Analisis of Macroeconomic Faktor Makroekonomi Terhadap Indeks Harga Saham di Jakarta Islamic Index (JII)XED - Huda, Miftahul; Suminto , Ahmad; Septiyani, Amelia; Hanif, Muhammad Nabil (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
The country’s economy slowdown causes the affected exchange rate or exchange rate to weaken, and Bank Indonesia’s interest rate policy at the time of the economic downturn decreases, it has an impact on the stock index in the JII. This research aims to determine the influence of macroeconomics on the IHS in JII. The method used is quantitative research, with an analysis model using the VAR technique. The data used is secondary data of a time series. The research results show that the influence of the ISSI and BI rate responded positively, while inflation responded positively. The exchange rate variable responded negatively to JII shocks until the end of the period. The results of the FEVD test show that the largest contribution was JII, inflation, ISSI, and BI rate, and the smallest contribution to JII was the exchange rate. Implication and recommendation this research are Bank Indonesia as the institution responsible for controlling inflation, can maintain inflation stability, lower the exchange rate against the dollar and maintain interest rate stability.